If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-5)=9x+5
We move all terms to the left:
2(3x-5)-(9x+5)=0
We multiply parentheses
6x-(9x+5)-10=0
We get rid of parentheses
6x-9x-5-10=0
We add all the numbers together, and all the variables
-3x-15=0
We move all terms containing x to the left, all other terms to the right
-3x=15
x=15/-3
x=-5
| 9x+4(4x+3)=4(6x+4)-4 | | (x^2+9)(x^2-4x+4+1)=0 | | 14=2(5m-3)+6 | | 6x=9x+15 | | -4(u+8)=-7u-26 | | 16y+4=8 | | 2(x-5)-5=-3(-4x+9)-x | | 2(3x-5)+3x=8 | | 5y^-60=5y | | 20=12+-2s | | 4x-+3(x-2)=21 | | -5p+8=38 | | x3-4x2+1=0 | | 9x+80=x+40 | | 4(x+8)=-6(3x-5)+6x | | 5/2x=10/x+2 | | 3z+10=9 | | 5^2x=200 | | -34=-8x+5(x-5) | | 5n-13=n+7 | | x/0.25x+1.5=3.5 | | 12x^2-288x+1296=0 | | 3x/2+5=2x | | |2x-11|=3 | | 32=12=4(z-1) | | 3(x-1)=5(2x-1) | | 4k+5-2k=3k+1 | | 15=2x-11 | | 1.5/12=18/x | | -7b^2+b=8 | | 4v-11=65 | | 10z=2 |